Sistema Integrado de Diagnose e Recomendação (DRIS) em produção de mudas de citrus - Rezende, Cláudia Fabiana Alves (2014)
One of the most competitive and growth potential of the agribusiness sector is the citrus industry. Citrus nurseries grown in protected cultivation, constitutes one of the foundations of this growth. To achieve high productivity in any culture, there are a number of factors, among which the supply of nutrients, in the manner and in adequate quantity becomes paramount. The Diagnosis and Recommendation Integrated System (DRIS) was developed to provide a diagnosis of the nutritional status of cultivated plants, helping the decision on fertilizer recommendation for crops, being based on the balance of essential nutrients to plants. The objective of this study aimed to obtain a database of foliar analysis for establishment of DRIS and assess the nutritional status of two rootstocks (Rangpur lime and Swingle Citrumelo) and two combinations of citrus seedlings (Orange Pear/Rangpur lime and Orange Christmas /Swingle Citrumelo) grown in ‘Goiás’ collections hundred twenty leaf samples for rootstocks and one hundred and twenty leaf samples for ready seedlings were performed . With the data obtained organized a database. The database was analyzed by the tracks or Critical Levels of Concentration and DRIS method by method. Bands Concentration diagnosed for the Rangpur Lime rootstock , the most limiting nutrient deficiency were Mg and Zn and excess P and Fe. For Citrumelo Swingle, limiting disability K, S, Mn, Cu and Zn, excess Fe and N. For the citrus nurseries K, S and Zn were the nutrients most limiting nutrient deficiency and P, Fe, Mg and N in excess. Zn is the nutrient most often deficiency and Fe excess among rootstocks and citrus nurseries. The DRIS diagnosed S as the most limiting disability and N as the most limiting for excess, and still showed higher sensitivity for diagnosing nutritional problems.